2007
DOI: 10.1016/j.jada.2007.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Three Food Frequency Questionnaires to Assess Dietary Calcium Intake in Adults

Abstract: All three FFQs performed reasonably well at estimating dietary calcium intake compared to food records; each may be appropriate for use in select clinical and research settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 36 publications
5
46
0
1
Order By: Relevance
“…Baseline Calcium Consumption We used the 25-item Short Calcium Questionnaire [29] to assess dietary calcium consumption at baseline. The Short Calcium Questionnaire has been shown to be a reliable method for estimating dietary calcium intake [29].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Baseline Calcium Consumption We used the 25-item Short Calcium Questionnaire [29] to assess dietary calcium consumption at baseline. The Short Calcium Questionnaire has been shown to be a reliable method for estimating dietary calcium intake [29].…”
Section: Methodsmentioning
confidence: 99%
“…The Short Calcium Questionnaire has been shown to be a reliable method for estimating dietary calcium intake [29]. For each food/beverage item listed (e.g., milk, any kind, including on cereal, in beverages, etc.-1 cup), participants entered the number of servings eaten in a typical week.…”
Section: Methodsmentioning
confidence: 99%
“…A similar difference in estimates of Zn intake between a seventy-four-item FFQ and a 7 d weighed record was also reported by Samman et al (29) . Although FFQ can both under-and overestimate nutrient intake, many validation studies have reported that FFQ overestimate nutrient intakes when compared with FR or 24 h recalls (34)(35)(36) . Of course, whether estimates of intake obtained using an FR are reliable cannot be known with certainty, but it is evident that our FFQ yielded consistently higher estimates of Zn intake than did the FR (as confirmed by Bland-Altman analysis).…”
Section: Relative Validitymentioning
confidence: 99%
“…In gen- 19 If even after dietary changes, calcium intake remains below ideal, supplements can be taken. Because of limits to intestinal absorption, no more than 500 -600 mg of calcium supplements should be consumed at one time.…”
Section: Nonpharmacologic Interventionsmentioning
confidence: 99%